Riwayat and dirayah in hadith studies: Muhammad Amim al-Ihsan’s methodology in Fiqh al-Sunan wa al-Athar as a case study / Muhammad Hosain - Muhammad , Hosain (2018)
Identifying the method of writing is important to help the reader or researcher to understand what the author of a book presented in his or her writing. This methodology can offer a preliminary overview of the content of the book as well as to detect the author’s approach in his or her authorship. This research aimed to achieve several objectives, namely to highlight the biographical account of Muḥammad ‘Amīm al-Iḥsān as well as identifying his published and unpublished authorships, i.e books, edited books, commentary and manuscripts written by him. Similarly, the study also discussed his thought and academic contribution. The researcher also identified and meticulously analyzed Iḥsān’s exclusive dirāyah and riwāyah in his method of writing in his celebrated book of ḥadīth Fiqh al-Sunan wa al-Athār. In addition, the study showed his benefits and contribution to the development of the study of al-Ḥadīth in Bangladesh. In this study, the researcher had utilized two main research methods, i.e data collection and analysis. During data collection, the researcher had carried out library research and some interviews, with no questionnaires since the main attention of the study was on the texts. Meanwhile, in data analysis, the researcher had used the deductive and inductive methods. The findings of this work are especially helpful for local and international readers or researchers. This study discovered much information about Iḥsān’s missing books. In authoring this book, Iḥsān employed various methods. In the same manner, the study also discovered his contribution and benefits to the development of the Ḥadīth studies in Bangladesh.